Laparoscopic Finding of Ectopic Adrenocortical Tissue in a 2-Year-Old Boy with Vanishing Testis - Antonio Marte (Georg Thieme Verlag KG, 2018)
Ectopic adrenocortical tissue (EAT) along the spermatic cord is an unusual condition in children. The author reports on a 2-year-old boy with impalpable testis. On laparoscopy, EAT was detected along the hypotrophic spermatic vessels and excised. These remnants should be removed to prevent hormone production or malignant transformation.